KEWENANGAN DIREKSI PERUSAHAAN UMUM DAERAH PASAR PALEMBANG JAYA (Solusi, 2022)
The Regional Public Company Pasar Palembang Jaya is a Regional Owned Enterprise that was formed to manage, manage markets and market facilities in the context of economic development and support the Palembang City Government budget and national economic growth. This writing discusses the duties and authorities of the directors of the Palembang Jaya Regional Public Company based on the Palembang City Regional Regulation Number 1 of 2021 concerning the Palembang Jaya Market Regional Public Company, as well as the responsibilities of the directors of the Palembang Jaya Market Regional Public Company in achieving company goals. The type of research is normative legal research, research by reviewing library materials in the form of laws, regulations relating to setting the duties, authorities and responsibilities of directors at the Regional Public Company Pasar Palembang Jaya. The duties and authorities of the Board of Directors at the Palembang Jaya Market Regional Public Company are regulated in Article 32 of the Palembang City Regional Regulation Number 1 of 2021 concerning the Palembang Jaya Market Regional Public Company. In general, the directors carry out their duties in good faith for the interests and business of Perumda Pasar. The Board of Directors is responsible for the Regional Public Company of Pasar Palembang Jaya in achieving the company's goals.